Balance assessment during squatting exercise: A comparison between laboratory grade force plate and a commercial, low-cost device - Mengarelli, A.; Verdini, F.; Cardarelli, S.; Di Nardo, F.; Burattini, L.; Fioretti, S. (Journal of Biomechanics, 2018)
balance through squatting exercise is a central part of many rehabilitation programs and sports and plays also an important role in clinical evaluation of residual motor ability. The assessment of center of pressure (CoP) displacement and its parametrization is commonly used to describe and analyze squat movement and the laboratory-grade force plates (FP) are the gold standard for measuring balance performances from a dynamic view-point. However, the Nintendo Wii Balance Board (NWBB) has been recently proposed as an inexpensive and easily available device for measuring ground reaction force and CoP displacement in standing balance tasks. Thus, this study aimed to compare the NWBB-CoP data with those obtained from a laboratory FP during a dynamic motor task, such as the squat task. CoP data of forty-eight subjects were acquired simultaneously from a NWBB and a FP and the analyses were performed over the descending squatting phase. Outcomes showed a very high correlation (r) and limited root-mean-square differences between CoP trajectories in anterior-posterior (r > 0.99, 1.63 ± 1.27 mm) and medial-lateral (r > 0.98, 1.01 ± 0.75 mm) direction. Spatial parameters computed from CoP displacement and ground reaction force peak presented fixed biases between NWBB and FP. Errors showed a high consistency (standard deviation < 2.4% of the FP outcomes) and a random spread distribution around the mean difference. Mean velocity is the only parameter which exhibited a tendency towards proportional values. Findings of this study suggested the NWBB as a valid device for the assessment and parametrization of CoP displacement during squatting movement.